PENGEMBANGAN MEDIA PEMBELAJARAN SISWA BERBASIS LECTORA INSPIRE SEBAGAI MULTIMEDIA INTERAKTIF PADA POKOK BAHASAN IKATAN KIMIA DI SMA/SEDERAJAT - Rosye Destiana Nurjannati; Betti Holiwarni; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to develop Lectora Inspire based learning media on the subject of chemical bonding for high school students / equal valid based on didactic aspects, technical aspects, and aspects of the construct. The method used is the Research and Development (RnD) with the development process using the model ADDIE (Analysis, Design, Development, Implementation and Evaluation). ADDIE model development study performed only to a point Development (Development), for the purpose of this study was limited to develop and produce a valid instructional media to be implemented based on an assessment of the validator. This study was conducted from March-November 2016. The result of the validation by media development validator obtained a percentage of average assessment of the three aspects of 79,66% (80%) in good category, and the percentage obtained from the students by 85,63% and 85,33% of the teachers, which are good to use. Based on the results of research and discussion can be concluded that the media-based learning Lectora Inspire developed on the subject of chemical bonds are valid for use in learning chemistry for high school students / equivalent.Keywords: Computer-Based Learning Media, Lectora Inspire, Institute of Chemistry.